Thermal sensitivity of Clostridium botulinum type C toxin. - Hubálek, Z. (Cambridge University Press, 1988)
A sterile suspension containing 950 mouse LD50 per ml of type C botulinum toxin was exposed for various periods to different temperatures. The time required for the 99% (hundred-fold) reduction of toxicity was more than 5 years at -70 degrees C or -20 degrees C, 6 months at +5 degrees C, 3 weeks at +20 degrees C, 2 weeks at +28 degrees C, 2 days at +37 degrees C, 9 h at +42 degrees C, less than 30 min at +56 degrees C, less than 20 min at +60 degrees C, and below 5 min at +80 degrees C. The results suggest that Clostridium botulinum type C toxin, if produced in an ecosystem of the mild climatic zone, might persist there over the winter season and cause the intoxication of vertebrates next early spring in the absence of further microbial toxigenesis.